Development of a Low Noise and Low Energy Consumption Alpha Spectroscopy Amplifier for 222Rn Gas Detection - Kuluozturk, M. F.; Ozgen, S.; Dogru, M. (Polish Acad Sciences Inst Physics, 2017)
Rn-222 gas is a member of U-238 decay chain, which is the most abundant in nature, and decays by releasing alpha particles with energy of 5.49 MeV. Various detection systems are used for radon gas detection in the research of natural radioactivity, health, geophysics etc. The detection systems need some electronics layers, like amplifier, analyser and data storage unit. These systems generally use mains voltage or self-battery and they are not useful for long-term field research because of energy consumption, which is relatively high. In this study, the development of a low energy consumption and low noise spectroscopy amplifier system for the detection of alpha radiation emitted by Rn-222 and its daughters is presented. Amplifying and pulse shaping stages were developed with nuclear electronic methods. Operating performance of amplifying and pulse shaping stages has been demonstrated with a series of electronic and radioactive tests (gain test, signal to noise ratio measurement, electronics calibration and energy calibration). Additionally, nuclear spectroscopic studies were performed for comparison of this system with other alpha spectroscopy systems.
3rd International Conference on Computational and Experimental Science and Engineering (ICCESEN) -- OCT 19-24, 2016 -- Antalya, TURKEY